2021
DOI: 10.5194/amt-14-133-2021
|View full text |Cite
|
Sign up to set email alerts
|

An in situ gas chromatograph with automatic detector switching between PTR- and EI-TOF-MS: isomer-resolved measurements of indoor air

Abstract: Abstract. We have developed a field-deployable gas chromatograph (GC) with thermal desorption preconcentration (TDPC), which is demonstrated here with automatic detector switching between two high-resolution time-of-flight mass spectrometers (TOF-MSs) for in situ measurements of volatile organic compounds (VOCs). This system provides many analytical advances, including acquisition of fast time–response data in tandem with molecular speciation and two types of mass spectral information for each resolved GC peak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 61 publications
1
39
0
1
Order By: Relevance
“…However, the PTR-TOF-MS cannot separate isomers and fragment ions of different origins; thus, the potential indoor formation of formaldehyde and acetaldehyde cannot be evaluated. Real-time separation of isomers requires a PTR-TOF-MS configured with a fast gas chromatograph ( Claflin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the PTR-TOF-MS cannot separate isomers and fragment ions of different origins; thus, the potential indoor formation of formaldehyde and acetaldehyde cannot be evaluated. Real-time separation of isomers requires a PTR-TOF-MS configured with a fast gas chromatograph ( Claflin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As PTR-MS has limited capability to distinguish between isomers, a portion of the VOCs pulled from the cuvettes can be trapped in adsorbent tubes for subsequent GC-MS analysis. Latest developments now allow to operate individual instruments in PTR-ToF-MS or in GC-PTR-ToF-MS (or electron impact-ToF-MS) mode, which makes the separate trapping of VOCs for GC-MS analysis unnecessary (Claflin et al, 2021). The VOC-SCREEN system also correlates VOC emissions with the physiological state of the plant by simultaneous measurements of CO 2 assimilation and transpiration rates.…”
Section: Screening Vocs As Phenotypic Traitsmentioning
confidence: 99%
“…If H 3 O + depletion is negligible, as is the case in this study, the abundance of [M+ H] + ion scales linearly with the concentration of M with a slope equal to the product of the species-dependent reaction rate constant k MH , drift time t, and the H 3 O + reagent ion abundance. The proton-transfer reaction is exothermic, and the ionization-induced fragmentation occurs to varying degrees (∼ 0 % to ∼ 100 %) as the result of dehydration, H 2 elimination, alkyl group loss, or HNO 3 loss (Claflin et al, 2021;Duncianu et al, 2017;Leglise et al, 2019;Pagonis et al, 2019;Yuan et al, 2017), which can be represented by the term F MH + . The observed intensity of any ion is also a function of the ion abundance, I MH + , and ion transmission efficiency, T MH + .…”
Section: Gas-phase Quantificationmentioning
confidence: 99%
“…For instance, a comparison of gas-phase measurements by nitrate ion atmospheric pressure chemical ionization, iodide ion chemical ionization, and the Vocus-PTR shows that they differ in the reported relative abundances of OH-TMB oxidation products (Wang et al, 2020). In addition, artefacts such as ion fragmentation are known to occur for PTR-based techniques (Yuan et al, 2017), which could be substantial (> 70 %) for limonene oxidation products (Claflin et al, 2021;Pagonis et al, 2019); the formation of [M+ H 2 O] + adducts in the EESI-TOF, which has been reported previously to occur to a minor extent (Lopez-Hilfiker et al, 2019), also contributes to the discrepancies between the EESI-TOF and Vocus-PTR. These uncertainties complicate our data interpretation but do not change the overall trend in the sensitivity estimation, as shown below in Fig.…”
Section: Near-molecular Response Factorsmentioning
confidence: 99%